Respon Tanaman Bawang Merah Terhadap Aplikasi Pupuk Organik Limbah Ikan Dengan Bioaktivator Lokal Rebung Bambu - Ikhsan Hasibuan; Irma Lisa Sridanti; Farida Aryani (Politeknik Negeri Lampung., 2025)
Currently, there were 24 provinces in Indonesia experiencing a deficit of shallots. In Bengkulu province, the deficit of shallots reached 83.37%. The productivity of shallots in this province was very low, which was less than 1 ton per hectare. This study aimed to evaluate the responses of growth and yield of shallots with the applications of fish waste-based organic fertilizer prepared with local and commercial bioactivators. The study was conducted with a Randomized Block Design in 2 factors and 3 replications. The first factor was the type of fish waste-based organic fertilizer prepared with different bioactivators, namely bamboo shoots and EM-4. The second factor was the dosages of fish waste-based organic fertilizer, namely 0, 10, 20, and 30 t/ha. The main findings from this study are as followed. Fish waste-based organic fertilizer prepared with bamboo shoot bioactivator had a better effect compared to EM-4 bioactivator in terms of plant height, number of shoots, number of bulbs, bulb diameter, fresh weight of bulbs and dry weight of bulbs. The dosage that gave the best effect was 30 tons/ha, where the increasing of the dosages was consistently increased all variables observed.